Effects of organic fertilizers on soil properties in arid zones and their mechanism of action - Liu, Qi; Yang, Lili; Ma, Long; Zhai, Yunlong; Wang, Desheng (Frontiers in Environmental Science, 2026)
China’s arid and semi-arid regions, encompassing approximately half of the nation’s landmass, exhibit notably poor soil quality compared to other regions. The application of organic fertilizers stands out as a crucial strategy for enhancing soil characteristics, boosting crop yields, improving agricultural product quality, and fostering environmental sustainability in these areas. This practice represents a primary avenue for enhancing cultivated land quality, remediating saline-alkali soil, reducing reliance on chemical fertilizers, and promoting sustainable agricultural practices in China. Organic fertilization plays a pivotal role in advancing the quantity and quality of cultivated land, serving as a key component of the ecological “trinity” protection system. Nevertheless, the diverse array of organic fertilizers available yields varying effects on soil and crops. Overall, the application of organic fertilizers tends to decrease soil pH (especially for initially alkaline soils), with an average reduction of 0.21 units, among which the pH improvement effects on saline-alkaline soils and gray desert soils are particularly prominent; the increase in soil organic carbon (SOC) ranges from 3.82% to 113.3%; it can increase soil electrical conductivity by 18%–35%, and exhibits significant improvement effects on soil bulk density (with an average reduction of 5.2%–22%) and aggregate structure (with an average increase of 49.95%–61.67% in mean weight diameter, MWD); notably, effects such as pH regulation, SOC enhancement, and bulk density reduction are closely related to the type and application rate of organic fertilizers. For crops, the sole application of organic fertilizers can already increase yields, but the combined application of organic fertilizers yields a more significant yield-increasing effect (with an increase range of 4.31%–123.3%). Consequently, this study synthesizes cuttingedge research on organic fertilizers, with a specific focus on their impact on arid soil and underlying mechanisms. By offering theoretical insights, this review aims to inform the judicious application of organic fertilizers in arid regions, while delineating future research directions in this critical domain.